2020
DOI: 10.1097/ju.0000000000000905.04
|View full text |Cite
|
Sign up to set email alerts
|

PD34-04 URETEROSCOPIC PERFORMANCE OF THULIUM FIBER LASER (SOLTIVE PREMIUM SUPER PULSED LASER TM ) FOR THE TREATMENT OF UROLITHIASIS: RESULTS OF THE FIRST CASE SERIES IN THE UNITED STATES

Abstract: We previously showed that nearly half the patients left with residual fragments (RFs) after URS experience a subsequent stone-related event (SE). We aimed to determine if a stone free state after URS is associated with a fewer SEs than those left with residual fragments.METHODS: After undergoing URS for renal and ureteral calculi between December 2015 and February 2017 167 patients (209 renal units, RUs) were prospectively enrolled. CT was obtained 6-8 weeks post-operatively. Patients were evaluated at subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…Despite the majority of the initial laboratory and clinical studies were from Russian researchers, many more recent studies were done by researchers all around the world, showing promising results [ 14 ▪▪ , 15 18 ]. Still, after evaluating our bibliographic search results, more than 40% of the recent published research on TFL is from Russian origin or has Russian researchers participating in it.…”
Section: Bibliographic Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the majority of the initial laboratory and clinical studies were from Russian researchers, many more recent studies were done by researchers all around the world, showing promising results [ 14 ▪▪ , 15 18 ]. Still, after evaluating our bibliographic search results, more than 40% of the recent published research on TFL is from Russian origin or has Russian researchers participating in it.…”
Section: Bibliographic Search Resultsmentioning
confidence: 99%
“…Settings such as, 1–1.5 J and 15–30 Hz for fragmentation and 0.1–0.3 J and 50–100 Hz for dusting in (micro-) PCNL, 0.1–0.2J with 15–30W for dusting in the kidney, 0.2–0.5J with 10–15W for dusting and fragmentation in the ureter, and 2–5J and 5–10 Hz for bladder stones treatment [ 38 , 41 , 46 ]. However, there are even reports of some authors using up to 500 Hz in the upper tract [ 15 ]. Yet, this is very preliminary data and the optimal laser settings are far from being established, needing future studies on it [ 8 ▪ , 47 ].…”
Section: Optimal Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial clinical experiences have demonstrated that the different laser settings used in the operating room are safe for patients. Many combinations of laser settings have been tested for ureteral, renal, and bladder stone lithotripsies presented in various conference abstracts [ 9 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] and in full-text clinical experiences [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ] ( Table 2 ). However, the ideal one has not yet been established.…”
Section: Resultsmentioning
confidence: 99%
“…Initial clinical experiences have confirmed that the use of a small TFL laser fiber gives a better instrument deflection, and therefore, the urologist is able to treat lower pole calyceal stones [ 21 , 25 ], even with an acute lower pole infundibulopelvic angle [ 21 ].…”
Section: Resultsmentioning
confidence: 99%